2018
DOI: 10.3727/096504018x15166193231711
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA GAS5 Promotes Proliferation, Migration, and Invasion by Regulation of miR-301a in Esophageal Cancer

Abstract: Long noncoding RNA (lncRNA) growth arrest-specific transcript 5 (GAS5) has been revealed to be associated with the progression of various cancers. However, the biological roles of GAS5 in esophageal cancer (EC) remain unclear. We aimed to thoroughly explore the functions of GAS5 in EC. The results showed that GAS5 expression was increased in EC cells (ECA109, TE-1, TE-3, and EC9706) compared to SHEE cells. Knockdown of GAS5 decreased cell viability, migration, and invasion and induced apoptosis in EC9706 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…Furthermore, the GAS5 /miR-21/ PTEN axis influences cisplatin resistance and chemosensitivity, in cervical cancer and non-small cell lung cancer (NSCLC), respectively [ 66 , 67 ]. The only study demonstrating oncogenic properties of GAS5 showed that it upregulated CXCR4 (C-X-C motif chemokine receptor 4) by competing for miR-301a, in turn activating Wnt/β-catenin and NF-κB (nuclear factor kappa B) signaling to promote proliferation, migration, and invasion in esophageal cancer [ 68 ], suggesting that GAS5 could exert opposing functions in a tissue-specific manner.…”
Section: The Links Between Long Noncoding Rnas and Micrornasmentioning
confidence: 99%
“…Furthermore, the GAS5 /miR-21/ PTEN axis influences cisplatin resistance and chemosensitivity, in cervical cancer and non-small cell lung cancer (NSCLC), respectively [ 66 , 67 ]. The only study demonstrating oncogenic properties of GAS5 showed that it upregulated CXCR4 (C-X-C motif chemokine receptor 4) by competing for miR-301a, in turn activating Wnt/β-catenin and NF-κB (nuclear factor kappa B) signaling to promote proliferation, migration, and invasion in esophageal cancer [ 68 ], suggesting that GAS5 could exert opposing functions in a tissue-specific manner.…”
Section: The Links Between Long Noncoding Rnas and Micrornasmentioning
confidence: 99%
“…It could sponge MIR301A to affect Wnt and NF-kB signaling pathways to promote cancer cell proliferation, migration and invasion but reduced cell apoptosis. 103 However, Ke et al insisted that GAS5 was an anticancer gene in esophageal tumor. Overexpression of GAS5 significantly impeded tumorigenesis via EMT.…”
Section: Snhgs In Esophageal Cancermentioning
confidence: 99%
“…GAS5 could interact with miRNAs to participate in the process of tumorigenesis [27]. Hence, we found that GAS5 could interact with miR-23a-3p through luciferase reporter gene and RNA immunoprecipitation.…”
Section: Discussionmentioning
confidence: 82%